Análisis técnico-económico de alternativas de conexión para Colectoras 2-3 y Cerromatoso (2021)
This report details the design of two connection alternatives between the Cerromatoso substation, which is located in the department of Córdoba, and Collectors 2 and 3, which are located in La Guajira. This 500 [KV] system aims to transport 2000 [MW] generated with the La Guajira wind farms from Colectora 2 and 3 to Cerromatoso. The two alternatives that were evaluated are: 1. Hybrid alternative in which there is an HVDC line from Cerromatoso to Colectora 2 and an HVAC line from Colectora 2 to Colectora 3. 2. MTDC alternative which connects Cerromatoso and Collectors 2 and 3 through HVDC lines in MTDC (Multiterminal Direct Current) configuration. To evaluate and compare the viability of each alternative, a technical-economic study was carried out based on the recommendations of the CIGRE Brochures, specifically in Brochure 388 Impacts of HVDC Lines on the Economics of HVDC projects [1] which presents the design and economic analysis of an HVDC VSC line.